2000
DOI: 10.1046/j.1439-0450.2000.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ovine Campylobacter Infection Determined by Numerical Analysis of Electrophoretic Protein Profiles

Abstract: The relationship of 50 Campylobacter strains isolated from aborted ovine foetuses, and the faeces of sheep, cattle and chickens were determined by numerical analysis of electrophoretic (SDS-PAGE) protein profiles. Comparison of protein patterns by numerical methods revealed differences between C. fetus ssp. fetus, C. jejuni, and C. coli strains as well as heterogeneity among isolates from different outbreaks. Isolates from each farm produced a distinct cluster and flocks from different locations were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…As similar strains are capable of causing abortions in poultry and cattle, these animals are also considered reservoirs of Campylobacter spp. (DIKER et al, 2000). The presence of birds on sheep farms increases the risk of lambs becoming infected in their first days of life (BROMAN et al, 2002;PAO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As similar strains are capable of causing abortions in poultry and cattle, these animals are also considered reservoirs of Campylobacter spp. (DIKER et al, 2000). The presence of birds on sheep farms increases the risk of lambs becoming infected in their first days of life (BROMAN et al, 2002;PAO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter spp. are considered to be commensal organisms in the intestinal tracts of wild and domestic animals including chickens and other avian species (Diker et al 2000). Epidemiological studies demonstrated that consumption of contaminated poultry meat is the major cause of human campylobacteriosis (Stern et al 2001(Stern et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter spp. are considered to be commensal organisms in the intestinal tracts of wild and domestic animals including chickens and other avian species (Diker et al. 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter türleri, çeşitli evcil ve yabani hayvanların normal bağırsak florasında bulunmakta ve bu hayvanlarda enterik infeksiyonlar ve genital sistem infeksiyonlarına neden olmaktadır (7,8,13,17). Termofilik Campylobacter'ler grubunda incelenen Campylobacter jejuni, C. coli ve C. lari türleri, dünyanın pek çok böl-gesinde insan ve hayvanlarda bakteriyel enterik infeksiyonların en sık rastlanan nedenleri arasında yer almaktadır (3,14,16).…”
Section: Introductionunclassified